Nucleic acids delivered by cationic phytoglycogen nanoparticles protect RTG-2 cells against VHSV-IVa infection - Shayne J. Oberhoffner; Leah Haile; Erin Cooper; Starla A. Richardson; Stephanie J. DeWitte-Orr (Comparative Immunology Reports)
The innate immune system defends against infection by recognizing conserved pathogen-associated molecular patterns (PAMPs). This study investigates the prophylactic use of synthetic PAMP analogues to stimulate innate antiviral responses in rainbow trout cells. Two commercial analogues were tested: high molecular weight polyinosinic:polycytidylic acid (HMW poly I:C), mimicking viral double-stranded RNA, and CpG-oligodeoxynucleotides (CpG-ODNs), based on unmethylated bacterial DNA. These nucleic acids were tested either singly or combined whether they could enhance innate immune responses in rainbow trout cells. Previous research showed that complexing HMW poly I:C with cationic phytoglycogen nanoparticles (Nanodendrix, NDx) enhanced antiviral protection. Here, we explored whether co-delivery of HMW poly I:C and CpG-ODN 2216, both complexed to a newly developed NDx formulation with a higher degree of substitution (DS 0.88), could further improve protection against viral hemorrhagic septicemia virus (VHSV-IVa). We characterized the new NDx formulation in terms of size and surface potential, and assessed its cytotoxicity, immunostimulatory capacity, and antiviral efficacy using rainbow trout gonadal (RTG-2) cells. None of the formulations were cytotoxic. HMW poly I:C, whether alone or complexed with NDx, significantly upregulated the antiviral gene Mx1. Notably, only NDx-complexed HMW poly I:C provided significant prophylactic protection against VHSV-IVa, as measured by viral titer reduction. The addition of CpG-ODN 2216, even when complexed to NDx, did not enhance this protective effect. These findings demonstrate that HMW poly I:C complexed with 0.88 DS NDx effectively stimulates antiviral responses and reduces viral burden in vitro. This work provides foundational insight into nanoparticle-mediated innate immune activation in fish, supporting the development of nanomedicine approaches to protect aquaculture species from viral diseases.